Hybrid Convergent Procedure for the Treatment of Persistent and Long-Standing Persistent Atrial Fibrillation: Results of CONVERGE Clinical Trial. (December 2020) - DeLurgio, David B.; Crossen, Karl J.; Gill, Jaswinder; Blauth, Christopher; Oza, Saumil R.; Magnano, Anthony R.; Mostovych, Mark A.; Halkos, Michael E.; Tschopp, David R.; Kerendi, Faraz; Taigen, Tyler L.; Shults, Christian C.; et al.
Abstract : Background: The limited effectiveness of endocardial catheter ablation (CA) for persistent and long-standing persistent atrial fibrillation (AF) treatment led to the development of a minimally invasive epicardial/endocardial ablation approach (Hybrid Convergent) to achieve a more comprehensive lesion set with durable transmural lesions. The multicenter randomized controlled CONVERGE trial (Convergence of Epicardial and Endocardial Ablation for the Treatment of Symptomatic Persistent AF) evaluated the safety of Hybrid Convergent and compared its effectiveness to CA for persistent and long-standing persistent AF treatment. Methods: One-hundred fifty-three patients were randomized 2:1 to Hybrid Convergent versus CA. Primary effectiveness was freedom from AF/atrial flutter/atrial tachycardia absent new/increased dosage of previously failed/intolerant class I/III antiarrhythmic drugs through 12 months. Primary safety was major adverse events through 30 days. CONVERGE permitted left atrium size up to 6 cm and imposed no limits on AF duration, making it the only ablation trial to substantially include long-standing persistent–AF, that is, 42% patients with long-standing persistent–AF. Results: Of 149 evaluable patients at 12 months, primary effectiveness was achieved in 67.7% (67/99) patients with Hybrid Convergent and 50.0% (25/50) with CA ( P =0.036) on/off previously failed antiarrhythmic drugs and in 53.5% (53/99) versus 32.0% (16/50; P =0.0128) respectively off antiarrhythmic drugs. At 18 months using 7-day Holter, 74.0% (53/72) Hybrid Convergent and 55% (23/42) CA patients experienced ≥90% AF burden reduction. A total of 2.9% (3/102) patients had primary safety events within 7 days, and 4.9% (5/102) between 8 and 30 days postprocedure. No deaths, cardiac perforations, or atrioesophageal fistulas occurred. All but one primary safety event resolved. Conclusions: The Hybrid Convergent procedure has superior effectiveness compared to the CA for the treatment of persistent and long-standing persistent atrial fibrillation. Registration: URL: https://www.clinicaltrials.gov ; Unique identifier: NCT01984346.